C-Reactive Protein Correlates with Negative Symptoms in Patients with Schizophrenia - Boozalis, Ted; Teixeira, Antonio L.; Cho, Raymond Young-Jin; Okusaga, Olaoluwa (Frontiers in Public Health, 2018)
Peripheral and CNS-localized inflammatory processes are hypothesized to contribute to the complex pathophysiology of schizophrenia. Elevated levels of the acute phase reactant C-reactive protein (CRP) have been observed in schizophrenia, yet relatively few studies have investigated the association between this inflammatory biomarker and psychotic symptoms in schizophrenia. This study is a pilot cross-sectional analysis investigating the relation of plasma CRP levels and the positive and negative symptoms of schizophrenia (the primary aim), assessed by the Positive and Negative Syndrome Scale (PANSS). A secondary analysis was also performed evaluating the potential association of CRP with cognitive function using the NIH Toolbox Cognitive Test Battery. After adjusting for age, sex, race and body mass index, a positive correlation was observed between CRP and PANSS negative symptoms (rho = 0.37, p = 0.05). There was no correlation between plasma CRP and any of the NIH Toolbox measures of cognitive function in the unadjusted or adjusted analyses. Though limited by a relatively small sample size and the unavailability of longitudinal data, the correlation between CRP and psychopathology in this sample of patients supports a role for inflammation in the pathophysiology of schizophrenia.